Draft Fourth Five Year Plan 1966 West Bengal - Planning Commission (Planning Commission, 1966)
Against the total estimated, cost of Rs.228.77 lakhs and provisional outlay of Rs.100.00 lakhs according to preliminary memorandum for the establishment and maintenance of 100 Seed farms, an outlay of Rs.100.00 lakhs has been proposed. With the reduction in the provision now proposed vis-a-vis the total estimated cost, it will be possible only to meet the spill over expenditure in respect of the farms set up under 3rd Five-Year Plan and to establish a few new farms during the current plan. There is, however, no programme for setting up any new Block seed farm during 1966-67, as per recommendations of the Planning Commission.
Government of West Bengal Development and Planning Department
Government of West Bengal Development and Planning Department